Muhammad Arif Jati Purnomo TANAH SEBAGAI BAHAN PEWARNA PURBA YANG RAMAH LINGKUNGAN - Muhammad Arif Jati Purnomo; Agung Cahyana (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
Traces of “ ancient colors “ have begun to be known to humans since humans still live in caves. Some artifactsfrom the past are still displayed beautifully in several caves scattered throughout the world with conditions thatare still very good. This means that the colors depicted on the cave walls are still very clearly visible in thedirection of the colors such as red, white, black and brown. They have used natural coloring agents derivedfrom biotic and abiotic natural resources, such as animals, plants and mineral rocks Ancient colors becamean inspiration idea for researchers to conduct more in-depth research on materials and techniques by utilizingrocks or minerals that are around us. Stone, soil, bones, mixed with animal oil or fat can become coloringagents that have their own characteristics. It is possible to develop the potential of ancient colors that exist(plants, animals, soil, water, and rocks / minerals) in the batik center area of Sragen Regency to be exploredinto batik works of a characteristic region. The purpose of this Artistic (Art creation) research is to create anatural coloring formula from ancient rocks as an environmentally friendly natural dye for batik and its applicationto batik cloth.